The Software Problem in Library Automation - Sacit Arslantekin (Türk Kütüphaneciliği)
Software selection in library automation occurs as a problem in our cuntry. Organizations and their personnal have to prepare themselves on this issue before software selection. Because software selection will effect the services in future, it is an important issue to be considered. The lack of qualification in software selection can be overcome by common work of organizations, associations and educational organizations which take part.